Urgensi Pembinaan Akhlak bagi Anak-Anak Pra Sekolah - Zaini, Ahmad (THUFULA, 2014)
Internet is one of advanced technology. In seconds information from anywhere in the world is very easy to access than before it was invented. It would be easily just by typing a single word trough media information searching. it will display the information we want, both the positive and negative information. The problem now is that children are also familiar with the Internet media. Therefore, parents must participate to control and supervise their children when they do surfing in cyberspace. In addition to intensive supervision, early moral development should be done, if we do not want to miss. Children have fundamental rights of life and education, including teaching right to obtain information, but certainly not all of the information that is given to them must be adapted to their age level. According to the Koran, the child can be grouped to four typologies, namely children as living jewelry world, children as a test, the child as an enemy, and the child as a light eye. This is where parents have an important role in the formation of character for her children. Parents are the first educators in the family environment. Father and mother have to share a role in nurturing their children. Both should help each other, hand in hand and compact so that the coaching process goes according to plan. The roles and stages in building character for children are for example first, to the children in the noble, second, to provide opportunities for children to practice the noble character, third, giving the responsibility in accordance with the child’s development, and the fourth, supervise and directing children to be selective in the mix.